From old markers to next generation: reconstructing the history of the peopling of Sardinia - Carla Maria Calò; Giuseppe Vona; Renato Robledo; Paolo Francalacci (Taylor & Francis Group, 2021)
Context For many years the Sardinian population has been the object of numerous studies because of its unique genetic structure. Despite the extreme abundance of papers, various aspects of the peopling and genetic structure of Sardinia still remain uncertain and sometimes controversial. Objective We reviewed what has emerged from different studies, focussing on some still open questions, such as the origin of Sardinians, their relationship with the Corsican population, and the intra-regional genetic heterogeneity. Methods The various issues have been addressed through the analysis of classical markers, molecular markers and, finally, genomic data through next generation sequencing. Results and conclusions Although the most ancient human remains date back to the end of the Palaeolithic, Mesolithic populations brought founding lineages that left evident traces in the modern population. Then, with the Neolithic, the island underwent an important demographic expansion. Subsequently, isolation and genetic drift contributed to maintain a significant genetic heterogeneity, but preserving the overall homogeneity on a regional scale. At the same time, isolation and genetic drift contributed to differentiate Sardinia from Corsica, which saw an important gene flow from the mainland. However, the isolation did not prevent gene flow from the neighbouring populations whose contribution are still recognisable in the genome of Sardinians.